Search for the lepton flavour violating decay B+ -> K+μ-τ+ using B*0s2 decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2020)
A search is presented for the lepton flavour violating decay B+ -> K+mu (-)tau (+) using a sample of proton-proton collisions at centre-of-mass energies of 7, 8, and 13 TeV, collected with the LHCb detector and corresponding to a total integrated luminosity of 9 fb(-1). The tau leptons are selected inclusively, primarily via decays with a single charged particle. The four-momentum of the tau lepton is determined by using B+ mesons from Bs20 -> B+K- decays. No significant excess is observed, and an upper limit is set on the branching fractionB(B+-> K+mu (-)tau (+))<3.9x10(-5)at90%confidence level.The obtained limit is comparable to the world-best limit.
Gesehen am 22.10.2020
Im Titel sind die Plus- und Minuszeichen hochgestellt
Im Titel ist "0" hochgestellt, "s2" tiefgestellt
LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, J. Marks, S. Neubert, A. Piucci, N. Skidmore, S. Stemmle, U. Uwer, A. Zhelezov [und 822 weitere]